2013
DOI: 10.1021/ol4013052
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Direct Arylation of C–H Bond To Construct Quaternary Carbon Centers: The Synthesis of Diarylfluorene

Abstract: A novel Pd-catalyzed C-H functionalization reaction was developed to construct a quaternary carbon center with high yield. This reaction provides an efficient method for the synthesis of 9,9'-diarylfluorenes by direct arylation of monoarylfluorene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Further studies demonstrated that pure aromatic hydrocarbons of anthracene 35 derivatives exhibit both electron and hole transporting properties [17][18][19] , and can be used as host emitter in OLEDs 20,21 . Due to their good conjugation and the lack of preferential moieties either for hole or for electron transport, pure aromatic hydrocarbons are expected to possess high and bipolar carrier 40 transport property, which is highly desired as host component in OLEDs, such as host for phosphors in phosphorescent OLEDs (PhOLED) [22][23][24] . During the past decades, hosts with bipolar transport ability for phosphorescent emitters have aroused great attention due to the promising device features of high 45 performance [25][26][27] and simple device structure 28 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further studies demonstrated that pure aromatic hydrocarbons of anthracene 35 derivatives exhibit both electron and hole transporting properties [17][18][19] , and can be used as host emitter in OLEDs 20,21 . Due to their good conjugation and the lack of preferential moieties either for hole or for electron transport, pure aromatic hydrocarbons are expected to possess high and bipolar carrier 40 transport property, which is highly desired as host component in OLEDs, such as host for phosphors in phosphorescent OLEDs (PhOLED) [22][23][24] . During the past decades, hosts with bipolar transport ability for phosphorescent emitters have aroused great attention due to the promising device features of high 45 performance [25][26][27] and simple device structure 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The geometry optimization was performed using the density functional theory (DFT) 38,39 of Gaussian 09 program under Becke's 3-parameters employing Lee-Yang-Perdew function (B3LYP) 40 with 6-31G (d*) basis set. 40 The synthetic routes for the four pure hydrocarbon molecules are described in Scheme 1 41 .All the solvents were distilled from appropriate drying agents prior to use. Commercially available reagents were used without further purification.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the palladium-catalysed arylation of fluorenes by the teams of Wu and Song, Xie, and Huang was reported to give diarylfluorenes (Fig. 1e)2829. Fluorene is more acidic and less sterically demanding than other diarylmethane derivatives.…”
mentioning
confidence: 99%